Characterization of nanoscale atomic motion of Si in polycrystalline Cu layer - Viktor Takáts; Eszter Bodnár; Yuri Kaganovskii; Tamás Fodor; József Hakl; Sándor Molnár; Márton Soha; Kálmán Vad (Heliyon, 2024)
Atomic migration of silicon through grain boundaries of a thin polycrystalline Cu film and island formation on the Cu surface were studied in the temperature range of 403–520 K. Samples used in these experiments was prepared on Si(111) wafers by room temperature magnetron sputtering and they consisted of amorphous Si layer (80 nm) and polycrystalline Cu layer (40 nm). The silicon layer served as the source layer of diffusion, while the copper surface was the accumulation surface. Detection of Si atoms on the accumulation surface after penetration through the Cu layer was made by low energy ion scattering spectroscopy and the grain boundary diffusion coefficient DGB was determined from the appearance time. The depth distribution of Si in the Cu film was analysed by secondary neutral mass spectroscopy. From this depth distribution, DGB was also determined. By scanning probe microscope and electron microscope measurements, it was experimentally detected that Si atoms on the Cu surface did not form a continuous layer. Instead, amorphous Si islands were formed at the accumulation surface with surface protrusions in their centres.